Pelatihan Zenius Education dalam Meningkatkan Kompetensi Guru Melaksanakan E-Learning di Sumatera Utara - Esther Febrina Ritonga; Syafruddin Pohan; Feni Khairifa (PERSPEKTIF, 2023)
The purpose of this study is to analyze the meaning construction of Zenius Education, the Zenius Education communication model and the Zenius Education training model in increasing teacher competency in implementing e-learning. This research was conducted with a qualitative descriptive method. The subjects in this study were Zenius Education and the informants were determined using a purposive technique, namely with the criteria of having conducted training for teachers in the North Sumatra region. The results obtained from this study found that the Zenius training for teachers has a positive meaning for increasing teacher digital literacy, motivating and lightening the teacher's burden on teaching digital. Several obstacles may occur during the training process, such as the teacher's low digital literacy, limited facilities and the internet, but the credibility of Zenius who trains can overcome these obstacles.